Kinetics and thermodynamic analysis in one-pot pyrolysis of rice hull using renewable calcium oxide based catalysts - Gan, D.K.W. (Elsevier Ltd, 2018)
Thermodynamic and kinetic parameters of catalytic pyrolysis of rice hull (RH) pyrolysis using two different types of renewable catalysts namely natural limestone (LS) and eggshells (ES) using thermogravimetric analysis (TG) approach at different heating rates of 10â100 K minâ1 in temperature range of 323â1173 K are investigated. Catalytic pyrolysis mechanism of both catalysts had shown significant effect on the degradation of RH. Model free kinetic of iso-conversional method (Flynn-Wall-Ozawa) and multi-step reaction model (Distributed Activation Energy Model) were employed into present study. The average activation energy was found in the range of 175.4â177.7 kJ molâ1 (RH), 123.3â132.5 kJ molâ1 (RH-LS), and 96.1â100.4 kJ molâ1 (RH-ES) respectively. The syngas composition had increased from 60.05 wt to 63.1 wt (RH-LS) and 63.4 wt (RH-ES). However, the CO2 content had decreased from 24.1 wt (RH) to 20.8 wt (RH-LS) and 19.9 wt (RH-ES). Â© 2018 Elsevier Ltd